Porous molecular sieve coated titanium dioxide delustering agent, delustering / semi-delustering nylon and preparation method
By wrapping porous molecular sieve on titanium dioxide, the problem of high photocatalytic activity of TiO2 is solved, the molecular weight and polymerization of nylon products are improved, its mechanical properties are optimized, and photoaging is slowed down.
Patent Information
- Application Number
- CN202411775956.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The existing TiO2 has high photocatalytic activity, resulting in low polymerization degree and low molecular weight of nylon polymers, affecting its mechanical properties and accelerating the photoaging of fibers.
By encapsulating the porous molecular sieve on the outside of the titanium dioxide, its dispersion and stability in the nylon polymer are improved and the photocatalytic activity is reduced.
It has achieved the improvement of the molecular weight and polymerization of nylon products, optimized its mechanical properties, and slowed down the photoaging process of fibers.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a porous molecular sieve-coated titanium dioxide matting agent, matting / semi-matting nylon and a preparation method thereof. Background Art
[0002] According to the classification of industry standards, nylon chips are generally divided into glossy (titanium dioxide mass percentage less than or equal to 0.05%), semi-matt (titanium dioxide mass percentage greater than 0.1% and less than 0.6%) and matt chips (titanium dioxide mass percentage greater than or equal to 1.2%) according to the mass fraction of titanium dioxide added to the nylon resin; these chips can be used to produce glossy, semi-matt and matt filaments and their engineering plastics respectively.
[0003] During the preparation of semi-dull / dull nylon, a certain amount of TiO2 needs to be added to achieve the purpose of semi-dull / dull. However, the added TiO2 is difficult to disperse evenly, which will have an adverse effect on the polymerization of the nylon polymer itself, causing the nylon polymerization to proceed in the direction of side reactions, or affecting its degree of polymerization, resulting in nylon products with low degree of polymerization and low molecular weight, and its tensile strength, impact strength and other indicators will also be affected. At the same time, ordinary ultrafine anatase titanium dioxide has high photocatalytic activity, can absorb light radiation to produce free radicals and peroxides, accelerate the photoaging of fibers, and cause the strength, elongation and other mechanical properties of the dull fiber to decline rapidly due to light.
[0004] Therefore, solving the high photocatalytic activity of TiO2, improving its stability, and avoiding the problem of nylon aging and deterioration of mechanical properties due to excessive activity are of great significance for the development of matte / semi-matt nylon materials. Summary of the invention
[0005] The purpose of the present invention is to provide a porous molecular sieve coated titanium dioxide matting agent, matting / semi-matting nylon and a preparation method to solve the problem of high photocatalytic activity and poor stability of existing TiO2.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a porous molecular sieve-coated titanium dioxide matting agent, comprising the following steps:
[0008] Sodium hydroxide, sodium aluminate, silicon dioxide and water are mixed, and then titanium dioxide is added and mixed to carry out a crystallization reaction to obtain a porous molecular sieve-coated titanium dioxide matting agent.
[0009] Preferably, in the above-mentioned method for preparing a porous molecular sieve-coated titanium dioxide matting agent, the dosage ratio of the sodium hydroxide and water is 4-8 g: 40-70 mL;
[0010] The mass ratio of sodium hydroxide to sodium aluminate is 4-8:2-3;
[0011] The mass ratio of sodium aluminate to silicon dioxide is 1:0.9-2.5;
[0012] The mass of the titanium dioxide is 5 to 30 wt% of the total mass of the sodium hydroxide, sodium aluminate, silicon dioxide and titanium dioxide;
[0013] The titanium dioxide is anatase titanium dioxide.
[0014] Preferably, in the above-mentioned method for preparing a porous molecular sieve-coated titanium dioxide matting agent, the temperature of the crystallization reaction is 80 to 120° C., and the time of the crystallization reaction is 10 to 30 hours.
[0015] The invention also provides a method for preparing a porous molecular sieve-coated titanium dioxide matting agent, and obtains a porous molecular sieve-coated titanium dioxide matting agent.
[0016] The present invention also provides a method for preparing dull / semi-dull nylon, comprising the following steps:
[0017] A porous molecular sieve-wrapped titanium dioxide matting agent, a bio-based nylon salt, a solvent, a catalyst and an antioxidant are mixed to obtain a mixed solution, and a polymerization reaction is carried out to obtain a matting / semi-matting nylon.
[0018] Preferably, in the above-mentioned method for preparing matt / semi-matt nylon, the concentration of the porous molecular sieve-wrapped titanium dioxide matting agent in the mixed solution is 0.1 to 5 wt%;
[0019] The concentration of the bio-based nylon salt in the mixed solution is 30 to 80 wt %;
[0020] The mass of the catalyst is 0.1 to 1 wt% of the total mass of the bio-based nylon salt and the solvent;
[0021] The weight of the antioxidant is 0.01-1 wt % of the total weight of the bio-based nylon salt and the solvent.
[0022] Preferably, in the above-mentioned method for preparing matt / semi-matt nylon, the catalyst is a phosphorus-containing compound, sodium hydroxide, toluene diisocyanate or a boric acid compound;
[0023] The antioxidant is tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate butyl pentaerythritol ester, dilauryl thiodipropionate, distearyl thiodipropionate, phenolic substances, amine substances, phosphite substances or thioester substances.
[0024] Preferably, in the above-mentioned method for preparing a matt / semi-matt nylon, the polymerization reaction includes a prepolymerization reaction and a final polymerization reaction;
[0025] The prepolymerization reaction conditions are: temperature of 120-200°C, time of 0.5-8h, pressure of 0.5-3MPa;
[0026] The final polymerization process comprises: carrying out the first stage reaction under normal pressure, and carrying out the second stage reaction under vacuum after the first stage reaction is completed;
[0027] The temperature of the first stage reaction is 250-290°C, and the time of the first stage reaction is 60-240min;
[0028] The temperature of the second stage reaction is 250-290° C., and the time of the second stage reaction is 10-60 minutes.
[0029] The invention also provides a method for preparing the matt / semi-matt nylon and the matt / semi-matt nylon obtained.
[0030] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0031] In the present invention, anatase TiO2 is modified and a layer of porous molecular sieve is wrapped on the outside, thereby solving the problems of TiO2 agglomeration, uneven dispersion and too strong reaction activity that accelerates aging of nylon fibers, eliminating its adverse effects on nylon, and thus obtaining a nylon product with high molecular weight, high degree of polymerization and excellent mechanical properties. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing a porous molecular sieve-coated titanium dioxide matting agent, comprising the following steps:
[0033] Sodium hydroxide, sodium aluminate, silicon dioxide and water are mixed, and then titanium dioxide is added and mixed to carry out a crystallization reaction to obtain a porous molecular sieve-coated titanium dioxide matting agent.
[0034] In the present invention, the specific process of the mixing is:
[0035] Dissolve sodium hydroxide in water, add sodium aluminate and stir, then add silicon dioxide.
[0036] In the present invention, the usage ratio of the sodium hydroxide and water is preferably 4-8 g:40-70 mL, more preferably 4.5-5.8 g:45-60 mL, and more preferably 5.0 g:50 mL.
[0037] In the present invention, the mass ratio of sodium hydroxide to sodium aluminate is preferably 4-8:2-3, more preferably 4.5-5.8 g:2.25-2.75, and more preferably 5.0:2.5.
[0038] In the present invention, the mass ratio of the sodium metaaluminate to silicon dioxide is preferably 1:0.9-2.5, more preferably 1:1.
[0039] In the present invention, the mass of the titanium dioxide is preferably 5-30wt% of the total mass of sodium hydroxide, sodium aluminate, silicon dioxide and titanium dioxide, more preferably 10-25wt%, and even more preferably 15-20wt%.
[0040] In the present invention, the titanium dioxide is preferably anatase titanium dioxide, and more preferably ultrafine anatase titanium dioxide;
[0041] The particle size of the ultrafine anatase titanium dioxide is preferably 0.1 to 5 μm, more preferably 0.5 to 4 μm, and even more preferably 1 to 3 μm.
[0042] In the present invention, the temperature of the crystallization reaction is preferably 80-120°C, more preferably 90-110°C, and more preferably 100°C; the time of the crystallization reaction is preferably 10-30h, more preferably 12-24h, and more preferably 15h.
[0043] In the present invention, after the crystallization reaction is completed, the method further comprises:
[0044] After the reaction is completed, the suspension is cooled to room temperature to obtain a suspension, which is centrifuged and then washed with water until the pH value is 7, and then dried after washing;
[0045] The drying temperature is preferably 60 to 100° C., more preferably 70 to 90° C., and more preferably 80° C.; the drying time is preferably 10 to 15 h, more preferably 11 to 14 h, and more preferably 12 h.
[0046] The invention also provides a method for preparing a porous molecular sieve-coated titanium dioxide matting agent, and obtains a porous molecular sieve-coated titanium dioxide matting agent.
[0047] The present invention also provides a method for preparing dull / semi-dull nylon, comprising the following steps:
[0048] A porous molecular sieve-wrapped titanium dioxide matting agent, a bio-based nylon salt, a solvent, a catalyst and an antioxidant are mixed to obtain a mixed solution, and a polymerization reaction is carried out to obtain a matting / semi-matting nylon.
[0049] In the present invention, the concentration of the porous molecular sieve-encapsulated titanium dioxide matting agent in the mixed solution is preferably 0.1 to 5 wt %, more preferably 2 to 4 wt %, and even more preferably 3 to 3.5 wt %.
[0050] In the present invention, the concentration of the bio-based nylon salt in the mixed solution is preferably 30 to 80 wt %, more preferably 50 to 65 wt %, and even more preferably 55 to 60 wt %.
[0051] In the present invention, the mass of the catalyst is preferably 0.1-1 wt % of the total mass of the bio-based nylon salt and the solvent, more preferably 0.2-0.7 wt %, and even more preferably 0.3-0.6 wt %.
[0052] In the present invention, the weight of the antioxidant is 0.01-1 wt % of the total weight of the bio-based nylon salt and the solvent, more preferably 0.05-0.8 wt %, and even more preferably 0.1-0.5 wt %.
[0053] In the present invention, the solvent is water.
[0054] In the present invention, the catalyst is preferably a phosphorus-containing compound, sodium hydroxide, toluene diisocyanate or a boric acid compound;
[0055] The phosphorus-containing compound is preferably phosphoric acid, sodium hypophosphite, phosphorous acid, hypophosphorous acid, alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid, aryl-substituted hypophosphorous acid, phosphorus-containing alkanes, phosphorus-containing aryl ester compounds, phosphorus-containing metal salts, and phosphorus-containing ammonium salts;
[0056] The alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid, aryl-substituted hypophosphorous acid, phosphorus-containing alkane, phosphorus-containing aryl ester compound, phosphorus-containing metal salt or phosphorus-containing ammonium salt is a common substance in the art and is not particularly limited;
[0057] The boric acid compound is preferably boric acid.
[0058] In the present invention, the antioxidant is preferably tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate butyl pentaerythritol ester (antioxidant 1010), dilauryl thiodipropionate (antioxidant DLTDP), distearyl thiodipropionate (antioxidant DSTDP), phenolic substances, amine substances, phosphite substances, thioester substances;
[0059] The phenolic substance is preferably monophenol, bisphenol, triphenol, polyphenol, hydroquinone or thiobisphenol;
[0060] The amine substance is preferably naphthylamine, diphenylamine, p-phenylenediamine or a quinoline compound;
[0061] The quinoline compounds are common substances in the art and are not particularly limited;
[0062] The phosphite substances are common substances in the art and are not particularly limited;
[0063] The thioester substances are common substances in the art and are not particularly limited.
[0064] In the present invention, the method for preparing the bio-based nylon salt comprises the following steps:
[0065] Under a protective atmosphere, pentamethylenediamine, aliphatic dibasic acid and a solvent are mixed and reacted to obtain a bio-based nylon salt solution, and the bio-based nylon salt solution is purified to obtain a bio-based nylon salt.
[0066] In the present invention, the protective atmosphere is preferably nitrogen.
[0067] In the present invention, the aliphatic dibasic acid is preferably succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid 、 Dodecanedioic acid, tridecanedioic acid, further preferably succinic acid, glutaric acid, adipic acid, pimelic acid or suberic acid, more preferably succinic acid, glutaric acid or adipic acid;
[0068] When the aliphatic dibasic acid is succinic acid, the bio-based nylon salt is nylon 54 salt;
[0069] When the aliphatic dibasic acid is glutaric acid, the bio-based nylon salt is nylon 55 salt;
[0070] When the aliphatic dibasic acid is adipic acid, the bio-based nylon salt is nylon 56 salt;
[0071] When the aliphatic dibasic acid is pimelic acid, the bio-based nylon salt is nylon 57 salt;
[0072] When the aliphatic dibasic acid is suberic acid, the bio-based nylon salt is nylon 58 salt;
[0073] When the aliphatic dibasic acid is azelaic acid, the bio-based nylon salt is nylon 59 salt;
[0074] When the aliphatic dibasic acid is sebacic acid, the bio-based nylon salt is nylon 510 salt;
[0075] When the aliphatic dibasic acid is undecanedioic acid, the bio-based nylon salt is nylon 511 salt;
[0076] When the aliphatic dibasic acid is dodecanedioic acid, the bio-based nylon salt is nylon 512 salt;
[0077] When the aliphatic dibasic acid is tridecanedioic acid, the bio-based nylon salt is nylon 513 salt.
[0078] In the present invention, the solvent is water or aliphatic alcohol, preferably ethanol.
[0079] In the present invention, the molar ratio of pentamethylenediamine to aliphatic dibasic acid is 1:1-3, more preferably 1:1-1.5, and more preferably 1:1.05-1.25.
[0080] In the present invention, the usage ratio of pentamethylenediamine to solvent is preferably 30-40 g: 200-300 mL, more preferably 32-39 g: 220-270 mL, and more preferably 36-38 g: 230-250 mL.
[0081] In the present invention, the temperature for the reaction of the pentamethylenediamine, aliphatic dibasic acid and solvent is preferably 30-120°C, more preferably 40-80°C, more preferably 50-60°C; the reaction time is preferably 0.5-2h, more preferably 0.75-1.5h, more preferably 1h.
[0082] In the present invention, the purification method is preferably to reduce the solubility of the bio-based nylon salt in the solution by cooling or adding a crystallizing agent to obtain a crystallized solid bio-based nylon salt, which is then filtered and vacuum dried.
[0083] In the present invention, the polymerization reaction includes a prepolymerization reaction and a final polymerization reaction;
[0084] The conditions of the prepolymerization reaction are as follows: the temperature is preferably 120-200°C, more preferably 150-180°C, and more preferably 160°C; the time is preferably 0.5-8h, more preferably 1-5h, and more preferably 2h; the pressure is preferably 0.5-3MPa, more preferably 0.6-2MPa, and more preferably 0.7MPa;
[0085] The final polymerization process comprises: carrying out the first stage reaction under normal pressure, and carrying out the second stage reaction by vacuuming for 10 to 60 minutes after the first stage reaction. The purpose of vacuuming is to extract the small molecular by-products produced during the final polymerization process, so as to make the nylon polymerize better and achieve a higher molecular weight and better mechanical properties.
[0086] The temperature of the first stage reaction is preferably 250-290°C, more preferably 260-280°C, and more preferably 270°C; the time of the first stage reaction is preferably 60-240 min, more preferably 80-200 min, and more preferably 120 min;
[0087] The temperature of the second stage reaction is preferably 250-290°C, more preferably 260-280°C, and more preferably 270°C; the time of the second stage reaction is preferably 10-60 min, more preferably 15-50 min, and more preferably 20-40 min.
[0088] The invention also provides a method for preparing the matt / semi-matt nylon and the matt / semi-matt nylon obtained.
[0089] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] Example 1
[0091] A method for preparing a porous molecular sieve-coated titanium dioxide matting agent comprises the following steps:
[0092] 5.0g of sodium hydroxide was dissolved in 50mL of deionized water and stirred until completely dissolved. Then, 2.50g of sodium aluminate was added. After the mixed solution was stirred evenly, 2.50g of silicon dioxide was added. Then, 2.50g of ultrafine anatase titanium dioxide with a particle size of 2μm was added. The obtained mixed solution was stirred at room temperature for 15h and crystallized at 90°C for 12h. After the reaction was completed, it was cooled to room temperature, and the obtained suspension was poured into a centrifuge tube, centrifuged, and the precipitate was washed with deionized water until the pH was equal to 7. Then, it was placed in an oven at 80°C and dried for 12h to obtain a porous molecular sieve-coated titanium dioxide matting agent.
[0093] Example 2
[0094] A method for preparing a porous molecular sieve-coated titanium dioxide matting agent comprises the following steps:
[0095] 7.05g of sodium hydroxide was dissolved in 70mL of deionized water and stirred until completely dissolved. Then, 2.53g of sodium aluminate was added. After the mixed solution was stirred evenly, 2.48g of silicon dioxide was added, and then 5.17g of ultrafine anatase titanium dioxide with a particle size of 2μm was added. The obtained mixed solution was stirred at room temperature for 15h and crystallized at 90°C for 12h. After the reaction was completed, it was cooled to room temperature, and the obtained suspension was poured into a centrifuge tube, centrifuged, and the precipitate was washed with deionized water until the pH was equal to 7, and then placed in an oven at 80°C for 12h to obtain a porous molecular sieve-coated titanium dioxide matting agent.
[0096] Example 3
[0097] A method for preparing nylon 56 salt comprises the following steps:
[0098] Under a nitrogen atmosphere, 50.90 g of adipic acid, 37.36 g of pentamethylenediamine and 250 mL of anhydrous ethanol were mixed and reacted at 60° C. for 1 h. After the reaction, the obtained product was cooled to 4° C., and the precipitated product was filtered and vacuum dried to obtain nylon 56 salt.
[0099] Example 4
[0100] 90.02 g of nylon 56 salt prepared in Example 3, 60.01 g of deionized water, 0.4501 g of sodium hypophosphite, 0.1500 g of antioxidant 1010 and 1.5030 g of the porous molecular sieve-coated titanium dioxide matting agent prepared in Example 1 were mixed, magnetically stirred for 1 hour and then ultrasonicated for 0.5 hour to obtain a mixed solution, and the mixed solution was transferred to a reactor and prepolymerized for 2 hours at 200° C. and 0.7 MPa. After the prepolymerization reaction was completed, the mixture was vented for 1 hour to normal pressure, and then reacted at 260° C. and closed normal pressure for 2 hours. After the final polymerization reaction was completed, the mixture was vacuumed and reacted at 260° C. for 10 minutes to obtain semi-dull nylon 56.
[0101] After testing, the molecular weight (Mn) of the semi-dull nylon 56 prepared in Example 4 is 23040, the relative viscosity is 2.56, and the tensile strength is 60 MPa.
[0102] Example 5
[0103] 90.38 g of nylon 56 salt prepared in Example 3, 60.25 g of deionized water, 0.4519 g of sodium hypophosphite, 0.1506 g of antioxidant 1010, and 3.7658 g of the porous molecular sieve-coated titanium dioxide matting agent prepared in Example 1 were mixed, magnetically stirred for 1 hour and then ultrasonicated for 0.5 hour to obtain a mixed solution, and the mixed solution was transferred to a reactor and prepolymerized for 2 hours at 200° C. and 0.7 MPa. After the prepolymerization reaction was completed, the mixture was vented for 1 hour to normal pressure, and then reacted at 260° C. and closed normal pressure for 2 hours. After the final polymerization reaction was completed, the mixture was vacuumed and reacted at 260° C. for 10 minutes to obtain semi-dull nylon 56.
[0104] After testing, the molecular weight (Mn) of the semi-dull nylon 56 prepared in Example 5 is 22307, the relative viscosity is 2.54, and the tensile strength is 59.2 MPa.
[0105] Example 6
[0106] 90.45 g of nylon 56 salt prepared in Example 3, 60.30 g of deionized water, 0.4523 g of sodium hypophosphite, 0.1508 g of antioxidant 1010 and 6.0300 g of the porous molecular sieve-coated titanium dioxide matting agent prepared in Example 2 were mixed, magnetically stirred for 1 hour and then ultrasonicated for 0.5 hour to obtain a mixed solution, and the mixed solution was transferred to a reactor and prepolymerized for 2 hours at 200° C. and 0.7 MPa. After the prepolymerization reaction was completed, the mixture was vented for 1 hour to normal pressure, and then reacted at 260° C. and closed normal pressure for 2 hours. After the final polymerization reaction was completed, the mixture was vacuumed and reacted at 260° C. for 10 minutes to obtain matte nylon 56.
[0107] After testing, the molecular weight (Mn) of the matte nylon 56 prepared in Example 6 is 21254, the relative viscosity is 2.53, and the tensile strength is 58.7 MPa.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a porous molecular sieve coated titanium dioxide matting agent, characterized in that: The following steps are involved: Sodium hydroxide, sodium aluminate, silicon dioxide and water are mixed, and then titanium dioxide is added and mixed to carry out a crystallization reaction to obtain a porous molecular sieve-coated titanium dioxide matting agent.
2. The method for preparing a porous molecular sieve-coated titanium dioxide matting agent according to claim 1, characterized in that: The dosage ratio of the sodium hydroxide to water is 4-8 g: 40-70 mL; The mass ratio of sodium hydroxide to sodium aluminate is 4-8:2-3; The mass ratio of sodium aluminate to silicon dioxide is 1:0.9-2.5; The mass of the titanium dioxide is 5 to 30 wt% of the total mass of the sodium hydroxide, sodium aluminate, silicon dioxide and titanium dioxide; The titanium dioxide is anatase titanium dioxide.
3. The method for preparing a porous molecular sieve-coated titanium dioxide matting agent according to claim 1, characterized in that: The temperature of the crystallization reaction is 80-120° C., and the time of the crystallization reaction is 10-30 hours.
4. The porous molecular sieve coated titanium dioxide matting agent obtained by the method for preparing the porous molecular sieve coated titanium dioxide matting agent according to any one of claims 1 to 3.
5. A method for preparing matte / semi-matte nylon, characterized in that: The following steps are involved: The porous molecular sieve coated titanium dioxide matting agent according to claim 4, bio-based nylon salt, solvent, catalyst and antioxidant are mixed to obtain a mixed solution, and a polymerization reaction is carried out to obtain matting / semi-matting nylon.
6. The method for preparing matt / semi-matt nylon according to claim 5, characterized in that: The concentration of the porous molecular sieve-encapsulated titanium dioxide matting agent according to claim 4 in the mixed solution is 0.1 to 5 wt %; The concentration of the bio-based nylon salt in the mixed solution is 30 to 80 wt %; The mass of the catalyst is 0.1 to 1 wt% of the total mass of the bio-based nylon salt and the solvent; The weight of the antioxidant is 0.01-1 wt % of the total weight of the bio-based nylon salt and the solvent.
7. The method for preparing matt / semi-matt nylon according to claim 6, characterized in that: The catalyst is a phosphorus-containing compound, sodium hydroxide, toluene diisocyanate or a boric acid compound; The antioxidant is tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate butyl pentaerythritol ester, dilauryl thiodipropionate, distearyl thiodipropionate, phenolic substances, amine substances, phosphite substances or thioester substances.
8. The method for preparing matt / semi-matt nylon according to claim 6 or 7, characterized in that: The polymerization reaction includes a prepolymerization reaction and a final polymerization reaction; The prepolymerization reaction conditions are: temperature of 120-200°C, time of 0.5-8h, pressure of 0.5-3MPa; The final polymerization process comprises: carrying out the first stage reaction under normal pressure, and carrying out the second stage reaction under vacuum after the first stage reaction is completed; The temperature of the first stage reaction is 250-290°C, and the time of the first stage reaction is 60-240min; The temperature of the second stage reaction is 250-290° C., and the time of the second stage reaction is 10-60 minutes.
9. The matt / semi-matt nylon obtained by the method for preparing matt / semi-matt nylon according to any one of claims 5 to 8.